2013
DOI: 10.4269/ajtmh.12-0381
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Household Family Members of Brucellosis Cases and Neighboring Community Members in Azerbaijan

Abstract: Abstract. Brucellosis is an endemic zoonotic disease in Azerbaijan. The first human brucellosis case reported in 1922 was in Pardabil village of a region currently named Shabran. Household members of brucellosis index cases are a population at risk for brucellosis infection. The purpose of this study was to determine the rate of seropositivity of brucellosis among household and neighboring community members of brucellosis index cases in Azerbaijan. Twentyone household members of 8 index brucellosis cases and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
11
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 7 publications
6
11
2
Order By: Relevance
“…In the South Caucasus region, males are more involved in the care and management of farm and domestic animals, and are more likely to be shepherds; this may explain the high disparity in brucellosis prevalence compared to females. A similar finding was also noted in Azerbaijan, a neighboring country [18]. Brucellosis can infect persons of any age, but in endemic areas most cases occur in young adults.…”
Section: Discussionsupporting
confidence: 80%
“…In the South Caucasus region, males are more involved in the care and management of farm and domestic animals, and are more likely to be shepherds; this may explain the high disparity in brucellosis prevalence compared to females. A similar finding was also noted in Azerbaijan, a neighboring country [18]. Brucellosis can infect persons of any age, but in endemic areas most cases occur in young adults.…”
Section: Discussionsupporting
confidence: 80%
“…Due to the common living area and the common food consumption, the risk of Brucella is increased in family members of index case family members. In previous studies, with the scanning of family members, the seropositivity rate was reported as 9.5% -36.8% and it was suggested that family members should be examined for Brucella [16,17]. In our study, brucella history rate of patients' family members was found to be 39.2%.…”
Section: Discussionsupporting
confidence: 49%
“…However, how to strictly implement the standard health quarantine is still a challenge for each cities including Quzhou. So far in practice the most common diagnostic method is still serology, as the gold standard diagnostic method (Ismayilova et al., ), i.e. Brucella culture, is time‐consuming and low positive rate (Špičić et al., ).…”
Section: Discussionmentioning
confidence: 99%